2002
DOI: 10.1088/0953-8984/14/44/331
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis of a high-pressure amorphous phase of SnI4

Abstract: We have performed a high-pressure synchrotron x-ray diffraction study of a metallic amorphous state in SnI 4 induced by pressure. The Faber-Ziman structure factor S(Q) was obtained from diffraction intensities measured at pressures between 25 and 65 GPa. The first peak in S(Q) is relatively intense and sharp and the second peak is overlapped with the third one. Such features are also found in S(Q) for pure metallic glasses of Ni and Fe at 1 atm but not in molecular liquids. The obtained reduced radial distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…This is consistent with previously reported measurements of pressure variations across SnI 4 samples loaded inside gasketed diamond cells. 4,14 Most of the samples in this experiment were taken to high temperature, which also reduces pressure gradients due to nonhydrostaticity ͑Table I͒.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…This is consistent with previously reported measurements of pressure variations across SnI 4 samples loaded inside gasketed diamond cells. 4,14 Most of the samples in this experiment were taken to high temperature, which also reduces pressure gradients due to nonhydrostaticity ͑Table I͒.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The total structure factors S(Q) obtained at pressures between 25 and 65 GPa [39] are shown in figure 12, together with data of liquid measured at 160 • C with 113 keV x-rays [40].…”
Section: High-energy X-ray Diffraction Under High Pressurementioning
confidence: 99%
“…Figure 12. Total structure factors S(Q) of SnI 4 at 25, 35, 45 and 55 GPa[39] during decompression together with liquid data obtained at ambient pressure (160 • C)[40].…”
mentioning
confidence: 99%
“…A dependence on the compression history is recognized in another study 21 : a second compression moves the frontier between Am-II and Am-I phases from 3 to 7 GPa upon compression, while in first compression CP-I was followed by CP-II and then Am-I. A following paper 22 studied specifically the structure of the amorphous state Am-I by X-ray scattering and it concluded that in this form of SnI 4 , the molecules dissociate leading to a state with great similarities with metallic glasses such as Ni or Fe, because the position of the maximum of radial distribution function does not coincide with the intramolecular atomic distances. The decomposition is supposed to occur above 25 GPa, and the coordination number deduced between 35 and 55 GPa, considering that Sn and I atoms are indistinguishable, is about 10.…”
Section: Introductionmentioning
confidence: 80%